Q: How would you simplify x 2 Parenthesis 3x 7 Parenthesis?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6x^2

y + 12 = -3(x - 2) y + 12 = -3x + 6 y = -3x - 6 or y = -3(x + 2)

3x = 5x - 10 Subtract both sides by 5x 3x - 5x = 5x - 10 - 5x Simplify - 2x = - 10 Divided both sides by -2 to isolate x - 2x / - 2 = - 10 / - 2 Simplify x = 5 Plug x into the original equation. 3(5) = 5(5) - 10 = ? Simplify 15 = 25 - 10 = ? Simplify 15 = 15 = ? Therefore 3x = 5x - 10 = 15

If that's 6x + 10, that factors to 2(3x + 5)

The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1

Related questions

It is: 2(3x-7y) = 6x-14y

(4x ^2 + 3) + (3x ^2 + 8) = ( 4x^2 + 3x^2 ) + (3+8) = 7x^2 + 11

To simplify (3x3)2, the exponent is distributed to both the constant and the variable and multiplied with any other exponents. So (3x3)2 = 32 * x3*2 = 9x6.

Assuming simplify = factor...x3 - 3x + 2 = (x-1)(x2+x-2)

(a^2+7a-8)/(a^2+6a-7) (original equation) (a+8)(a-1)/(a+7)(a-1) (simplify top and bottom) (a+8)/(a+7) <--answer

2

3x(12x-2) is equivalent to 36x^2 -6x simplified

the answer is 3 and here's why 3x-2=7 add 2 to both sides of the equation (3x-2)+2=7+2 simplify 3x=9 divide both sides by 3 3x/3=9/3 simplify x=3

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

6x^2

2 times (3x) all you need to do is destribute the 2 2 times 3 is 6 so the answer is 6x

3X + 7 - X + 2 = 2X + 9